La evaluación en el aprendizaje integral de las niñas de tercero y cuarto año de educación básica, de la Escuela OEA, del cantón Santo Domingo, parroquia Abrahán Calazacón, durante el año lectivo 2011-2012 - Armijo Mora, Sonia Isabel (2012)
This Research Project on Strategies for Evaluation in the Integrated Learning girls in third and fourth year Basic Ed, I performed at School "OAS" Canton Santo Domingo, Abraham Calazacón parish during the school year 2011-2012, in order to verify whether this educational institution and in the years studied using assessment strategies that allow a holistic learning in students. We present the topic, background research, the respective justification that includes critical issues and objectives that address research, as well as the assumptions and their respective variables are treated, supported and clarified in the theoretical framework . As a result it started our research, thinking at all times aware and committed teachers to open to change and accept an innovative proposal for the development of comprehensive learning assessment in girls, whereas in study strategies to help check the effectiveness or failure of the teaching-learning, with the results for change in methodology and teaching material for improved school performance. Achieving a comprehensive learning in children is paramount at the present time educators grow in the effort to improve teaching aids, designed to optimize the comprehensive learning of students, yet assessment strategies that teachers use are still the same ie still apply traditional assessment through written examinations have always shown a high degree of passivity in students, which are tedious and stressful, because at presentation to an examination girls become fearful, it arises urge to use in teaching a range of assessment strategies in keeping with the times in which we find ourselves looking to get a fun job, happy for the students, showing interest in being assessed, because the results help to improve processes in the international student learning and will be consistent with the methodology used in the work of the teacher teaching.